(3GdGSJHUGQ aj YLGFH GdCeUGQs
(3ChdgG (B:s
(3hHYO aEfg deG cGf GdYde CfaS eG jbJfi s
(3BNQgG (B:s
(3PcQ HdGO GdeZQH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B70s
Keywords: (3GdLZQGajG h GdHdOGfs